Tāmarai moṭṭukaliṉ nēci : Ēmi Kārmaikkal eṉṟa Kāruṇya ammāḷ - Āṉantā, Tiyākarāj (Ṭōṉāvūr Aikkiyak Kūṭṭam, 1953)
Biography of Amy Carmichael, 1867-1951, Christian missionary from Ireland who served in Tamil Nadu.